The Effectiveness of Applying STEM Approach to Self-Efficacy and Student Learning Outcomes for Teaching Newton's Law - Irmawati Ibnah Muthi'ik; Abdurrahman Abdurrahman; Undang Rosidin (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2018)
This research aimed to determine the effectiveness of STEM learning approaches to self efficacy and student learning outcomes in Newton Law material. The design of this research is Quasi-Experiment with One Group Pretest-Posttest Design. The data obtained in this study are self efficacy data and student learning outcomes. Self efficacy result data was obtained through self efficacy scale is given before and after learning using STEM approach. While the data of student learning outcomes obtained through the question of the form of plural choices and essays given to students before and after learning using the STEM approach. Based on the research above, the average value of N-gain in self efficacy and students’ learning outcomes before and after being taught through learning using STEM approach. The average gain of n-gain in self efficacy and students' learning outcomes have increased with moderate category The result showed that STEM learning approach was effective to improve self efficacy and student’s learning outcomes.